Félix: a Late Pleistocene White Whale (Delphinapterus Leucas) Skeleton From Champlain Sea Deposits at Saint-Félix-de-Valois, Québec - Harington, C.; Lebel, Serge; Paiement, Maxime; de Vernal, Anne (Géographie physique et Quaternaire, 2006)
AbstractA nearly complete, articulated skeleton of an old white whale (Delphinapterus leucas) from Champlain Sea deposits at Saint-Félix-de-Valois is the best preserved specimen of its kind recorded from North America. It is one of 21 white whale specimens known from Champlain Sea deposits. Collagen from a vertebra yielded an accelerator mass spectrometry radiocarbon date of 10 700 ± 90 BP, which, with stratigraphic and paleoenvironmental data, is in accord with our knowledge of the past distribution of this species, its known habitat and habits. This study quantitatively traces regional sea-surface temperature, salinity and ice-cover. Dinocysts indicate a change from cold to cool conditions in surface water during that period corresponding to the withdrawal of ice and the beginning of the Holocene.